Wage and Price Controls in a Dynamic Macro Model - Possen, Uri M. (Econometrica, 1978)
Wage and price controls in the form of inflation ceilings are introduced into a dynamic extension of a variant of the IS-LM model. The controls do not alter the location of the equilibrium; rather, they affect the path and speed of adjustment of the economy. When slack exists, controls can be useful for lowering the rate of inflation and increasing employment and aggregate demand. However, when excess demand is present, controls although reducing the excess demand pressures and lowering the inflation rate may necessitate some form of commodity rationing. AN ISSUE THAT has recently received a great deal of attention is the effectiveness of wage and price controls as a macroeconomic policy tool. This paper studies the question in order to determine whether the view that controls are useful has a theoretical basis. Controls as introduced here are considered a means by which the government can affect the path of adjustment of the economy towards the equilibrium, and not an instrument by which the government can alter the location of the equilibrium itself. It is argued that if the economy faces cost-push type of inflation, where the actual inflation rate is above the equilibrium inflation rate, and the economy is adjusting to the equilibrium at a pace considered too slow, the institution of controls can result not only in a fairly rapid reduction in the rate of inflation but also some increase in employment. On the other hand, if the economy faces demand-pull inflation controls can prevent the economy from moving to an undesirable equilibrium and in the process reduce excess demand pressures although not eliminate them. As indicated above, for a macro model to be suitable for studying this problem, it is necessary both that it allow for inflation and that it be dynamic, in the sense of yielding information about not only equilibrium values but also the adjustment path of the economy. The formulation utilized adds to a variant of the IS-LM model a Phillips curve, a government balance equation, and an equation to indicate how inflationary expectations adjust. These additions make the IS-LM model dynamic and also incorporate wage and price inflation into that framework. This paper follows the tradition of Lipsey [1] in assuming that the Phillips curve is a labor market equation that relates the actual rate of wage inflation to the employment rate (or unemployment rate) and the expected rate of inflation. The government balance equation insures that government outflows equal government inflows. For example, when government expenditures exceed tax collections, the government must increase the size of its outstanding nominal debt to make up the difference. Finally, it is assumed that the expected rate of price inflation adapts towards the actual rate.